Keabsahan Perjanjian dengan Klausul Baku - Tessa Kurniawan (Nagari Law Review, 2018)
The application of standard contract, as at the beginning of its establishment has been creating a controversy related to its existence as well as its legal standardized contract. Indonesian Civil Code (KUHP perdata) does not specifically regulate the standard. The research is focused on two problems which are; the legality of agreement using standard clause and the absence of freedom of contract principle. This research is a normative research that is referred to the constitutional regulation and jurisprudence using legal material both primary and secondary. The legal material is compiled through literacy study which is qualitatively analyzed. This research has concluded; first, the agreement contains of standard clause is no longer being mattered whether it is legal or illegal agreement. However, the more important point is the rationality of the standardized clause substance. Second, normatively, there is no legal effect as the result of the absence of freedom of contract principle in the agreement.